Zoledronate upregulates MMP-9 and -13 in rat vascular smooth muscle cells by inducing oxidative stress - Arun MZ; Reel B; Sala-Newby GB; Bond M; Tsaousi A; Maskell P; Newby AC (Dove Medical Press, 2016)
Mehmet Zuhuri Arun,1 Buket Reel,1 Graciela B Sala-Newby,2 Mark Bond,2 Aikaterini Tsaousi,2 Perry Maskell,2 Andrew C Newby21Department of Pharmacology, Faculty of Pharmacy, Ege University, Izmir, Turkey; 2Bristol Heart Institute, University of Bristol, Bristol Royal Infirmary, Bristol, UK Background: Bisphosphonates, including zoledronate, target osteoclasts and are widely used in the treatment of osteoporosis and other bone resorption diseases, despite side effects that include damaging the stomach epithelium. Beneficial and adverse effects on other organ systems, including the cardiovascular system, have also been described and could impact on the use of bisphosphonates as therapeutic agents. Vascular smooth muscle cells (VSMCs) are major constituents of the normal vascular wall and have a key role in intimal thickening and atherosclerosis, in part by secreting MMPs that remodel the extracellular matrix and cleave cell surface proteins or secreted mediators. In this study, we investigated the effects of zoledronate on MMP expression.Methods: Rat VSMCs were stimulated by PDGF (50 ng/mL) plus TNF-α (10 ng/mL) or left unstimulated for a further 24 hours in serum-free medium. In other series of experiments, cells were pre-treated either with SC-514 (50 µM) or with apocynin (20 nM) for 2 hours, then zoledronate (100 µM) was added into 2% fetal calf serum containing medium for 24 hours.Results and discussion: Using isolated rat VSMCs in culture, zoledronate (100 µM) increased MMP-9 and -13 mRNA expressions but inhibited MMP-2 expression. MMP-9 and MMP-13 up-regulation was shown to depend on the NF-κB pathway; and this was activated by zoledronate. Furthermore, zoledronate elevated the levels of reactive oxygen species detected by either dichlorofluorescein in isolated VSMCs or lucigenin enhanced chemiluminescence in rat aortic rings in vitro. Apocynin, an inhibitor of NADPH oxidase, reversed NF-κB activation and MMP-9 and MMP-13 up-regulation by zoledronate.Conclusion: We conclude that zoledronate increases MMP-9 and MMP-13 expressions in rat VSMCs dependent upon stimulation of the NF-κB pathway by reactive oxygen species. Effects on MMP expression may contribute to the pharmacologic profile of bisphosphonates.Keywords: vascular smooth muscle cell, matrix metalloproteinase, bisphosphonate, reactive oxygen species, zoledronate